Map of Alaska : showing latest explorations by U.S. Geological Survey and U.S. Coast and Geodetic Survey - National Geographic Society (U.S.) (1914)
Also shows railroads and volcanoes over printed in red.; Relief shown by hachures and spot heights.; Inset: Western extension of Aleutian Islands. This archival material has been provided for educational purposes. Ball State University Libraries recognizes that some historic items may include offensive content. Our statement regarding objectionable content is available at: https://dmr.bsu.edu/digital/about